Tweeting democracy: analyzing twitter's role in public participation during the Philippine election 2022 - Tenorio, Christine B.; Daud, Yammie Palao; Lubos, Lalevie Casas (Department of Government Studies Universitas Muhammadiyah Makassar, 2024)
This study displays Twitter's relevance in collecting sentiments and evaluating social networks, notably in election processes. This study examines 10,000 tweets on the 2022 Philippine presidential election, gathered during the key week of May 9–13, 2022, to show Twitter's influence in molding the public conversation. The study found the most popular hashtags, including #halalan2022 and #eleksyon2022, highlighting their importance in the digital discussion around the election. A thorough social network study established eight key communities, demonstrating a strong connection among Filipino netizens during election-related debates. Among these, noteworthy people such as @RexelBartolome and @daywreckoning, as well as the news site @ABSCBNEWS, emerged as essential nodes, demonstrating their influence in information dissemination. Sentiment analysis of the tweets revealed a mostly neutral public mood toward the election, with frequent phrases such as